P47 Patient characteristics of those referred and not referred for early post-hospitalisation pulmonary rehabilitation. (14th November 2013) - Jones, SE; Kon, SSC; Green, SA; Bell, D; Canavan, JL; Nolan, CM; Clark, AL; Dickson, M; Nolan, A-M; Fleming, S; Haselden, M; Man, WD-C
Abstract : Background: Early post-hospitalisation pulmonary rehabilitation (PR) following acute exacerbation of COPD (AECOPD) has been shown to improve health-related quality of life (HRQOL), increase exercise capacity and reduce rate of hospital readmission. However, only a minority of eligible patients are referred for (or receive) this intervention. The aim of this study was to determine differences in baseline characteristics between those referred or not referred for early post-hospitalisation PR. We hypothesised that those with poorer lung function, worse functional capacity, increased muscle weakness and cachexia would be less likely to be referred for early post-hospitalisation PR. Methods: Two hundred and twenty six patients hospitalised for AECOPD were consecutively recruited on day of hospital discharge. All fulfilled the eligibility criteria for PR, which included the ability to walk 5 metres independently. The following measurements were performed on day of hospital discharge by the research team: spirometry, anthropometry (body mass index: BMI and fat free mass index (FFMI)), lower limb muscle strength (Quadriceps Maximum Voluntary Contraction: QMVC), functional capacity (4-metre gait speed (4MGS)), HRQOL (COPD Assessment Test (CAT)) and Hospital Anxiety and Depression scale (HAD)). Length of stay (LOS), previous admissions to hospital in past year, social deprivation scores (based on postcode) and smoking history were also recorded. The decision to refer was made by the clinical team, blinded to results of outcome measurements. Results: The results are seen in Table 1 . Seventy three patients (32%) were referred for early post-hospitalisation PR. Contrary to our hypothesis, there was no difference in spirometry, muscle strength, functional capacity or muscle mass between patients that were referred or not referred for early post-hospitalisation PR. There were also no differences in HRQOL, anxiety or depression scores, smoking status, social deprivation score or number of hospitalisations in past year. The only significant difference was a slightly reduced length of hospital stay for those referred to PR Conclusion: Reasons for non-referral for post-hospitalisation PR cannot be simply explained by physiological characteristics at hospital discharge, and are likely to be secondary to complex interactions between patient and healthcare professionals. Further qualitative work is required to understand these interactions and relationships.